РАННІ УСКЛАДНЕННЯ ДЕКОРТИКАЦІЇ ЛЕГЕНІ У ХВОРИХ З НЕСПЕЦИФІЧНОЮ ЕМПІЄМОЮ ПЛЕВРИ: ПРИЧИНИ, МЕТОДИ ПРОФІЛАКТИКИ (World Science, 2020)
We sorted out three groups of complications after perform an decortications of lung, developing in early post operational period: 1) the complications are caused by the technique of operations and anesthesia; 2)complications are caused by ineffective making of comprehensive treatment in post operational period; 3) combined complications. Making comprehensive treatment in preoperative and post operational period, making decortications of lung under visual control, making adequate ventilation during a time of operation, early sanitization of trachebronchialis tree and active patients after an operation, are measures of preventive complications by this patient group.